1985
DOI: 10.1111/j.1464-410x.1985.tb07015.x
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Coagulum Nephroithotripsy: a New Approach

Abstract: Intrarenal scatter of stone fragments during percutaneous nephrolithotripsy is a complication which may predispose to post-operative pain and further stone formation. The use of a coagulum to prevent such a complication has proved difficult when introduced percutaneously. This experimental study describes a new gelatine (Lithogel) which is introduced through the nephroscope to coat the renal calculus; it allows easy disintegration of the calculus within the gel, is safe to use and effectively prevents the scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1987
1987
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The success of PNL surgery ranges between 72-98% in published large-scale studies. The first large-scale study to report a 98% success rate was the study by Hasun et al conducted on 1000 cases in 1985 (7). In the first PNL studies conducted in our country, complete clearance of the stones has been reported as 60%, 77% and 87% respectively by Müslümanoğlu et al, Ünsal et al, and Ötençtemur et al (8-10).…”
Section: Discussionmentioning
confidence: 97%
“…The success of PNL surgery ranges between 72-98% in published large-scale studies. The first large-scale study to report a 98% success rate was the study by Hasun et al conducted on 1000 cases in 1985 (7). In the first PNL studies conducted in our country, complete clearance of the stones has been reported as 60%, 77% and 87% respectively by Müslümanoğlu et al, Ünsal et al, and Ötençtemur et al (8-10).…”
Section: Discussionmentioning
confidence: 97%
“…Coagulum formulations are "thick" mixtures that bind coarse particles together, so that the mass can be removed percutaneously (Miller, 1983;Hasun et al, 1985). By contrast, the proposed "excluding" formulations, herein described, would be "thin" solutions intended to flush out fine particles.…”
Section: Discussionmentioning
confidence: 99%
“…This problem was foreseen by Miller (l983), who recommended percutaneous lithotripsy as an alternative technique that would facilitate removal of the fragmented stone, preferably as a coagulum (Watson et al, 1983;Miller et af., 1984). Subsequent results confirmed this view and percutaneous methods have achieved a 94 to 99% rate of stone-free status (Reddy et al, 1985), while coagulum mixtures with improved qualities are being developed (Hasun et al, 1985). Extracorporeal shockwave lithotropsy places greater reliance upon the spontaneous passage of the stone fragments, but less than 75% of patients are rendered stone-free (Lingeman et al, 1985 ;Wickham et af., 1985).…”
mentioning
confidence: 99%